Methodological Approaches for Workplace Research and Management - Chiara Tagliaro; Marko Orel; Ying Hua (CRC Press, 2023)
This book explores a wide range of methodological approaches to examining various forms of workplace physical environments. It focuses on pressing questions regarding the relationship between the spatial component of the workplace, including its progressive hybridisation with other physical and virtual places, and its users, be they public organisations, private companies, or start-up businesses and solopreneurs. International contributors address a range of methods that are applicable both in research and practice to confront the most cutting-edge workplace-related issues. The assumption is that work has been changing, thanks to the virtualisation of many activities, and that homeworking and hybrid working modes are expected to increase significantly after Covid-19. Thus, spaces hosting work need to adapt accordingly. Researchers and practitioners have been struggling to determine how much space will be needed by companies, what kind of space will better host different work activities, which workers are more suited for working from home, and which instead are more productive if they have an office-based working arrangement. The necessary evolution of the office should follow evidence-based decisions on the abovementioned matters, which are only possible through rigorous investigations. This volume aims to support these investigations, which call for inventive applications of qualitative and quantitative methodologies. By doing so the book will encourage solid practices and thorough research agendas in workplace design, management, and use. Contributions come from different disciplines, including facilities management, real estate management, psychology, design, architecture, sociology, and organisation studies. Chapters highlight the importance of appropriate methodologies, borrowed from different fields, in addressing contemporary questions and developments in workplaces. By analysing the challenges and opportunities for conducting rigorous research in different workplace settings, this book will be critical reading for both academics and students, as well as for decision-makers and professionals who deal with workplace design and management.
Keywords: 650; Autoethnography; Built environment; Cluster Analysis; Consumer studies; Delphi; Digital ethnography; Expert-based interviewing; Facilities management; Interdisciplinary; Methodology; Mixed methods; Office management; Primary research; Qualitative; Quantitative; Real estate; Research framework; Research methods; Research models; Secondary research; Service blueprints; Social Network Analysis; Spatial Network Analysis; Spatial walkthroughs; curve mapping; and card sorting; Stated-Preference Analysis; Time Utilisation Surveys; Transdisciplinary; Value Focused Thinking; Workplace